Exploring printmaking for young people - Daniels, Harvey, 1936-; Turner, Silvie, 1946- (New York : Van Nostrand Reinhold Company, 1972)
Explains the techniques and instruments used in such processes as lithography, silk-screen, and intaglio
Bibliography : p. 93-95
Keywords: Prints -- Technique -- Juvenile literature